2017
DOI: 10.1111/ejh.12940
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of Pim‐3 kinase in adult T‐cell leukemia

Abstract: Pim-3 is a potentially suitable target for the development of novel therapeutic agents against ATL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The expression of PIM2 kinase was found to be higher in MM than in any other cancer type[14]. Recent research showed that inhibition of PIM2 kinase has significant anti-tumor efficacy in multiple myeloma[15] and that targeting PIM3 may have activity against adult T-cell leukemia[16]. It has also been reported that PIM1 mRNA expression is a potential prognostic biomarker in acute myeloid leukemia[17].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PIM2 kinase was found to be higher in MM than in any other cancer type[14]. Recent research showed that inhibition of PIM2 kinase has significant anti-tumor efficacy in multiple myeloma[15] and that targeting PIM3 may have activity against adult T-cell leukemia[16]. It has also been reported that PIM1 mRNA expression is a potential prognostic biomarker in acute myeloid leukemia[17].…”
Section: Introductionmentioning
confidence: 99%
“…Very few previous studies have evaluated the expression and function of PIM3 in AML. 21,22 Here, we revealed a high level of PIM3 expression in AML cells relative to healthy donor PBMCs. Moreover, we observed distinctive expression patterns of PIM1, PIM2, and PIM3 in AML, 10,11,13,22 and our results suggest that PIM3 expression is subject to regulation via a unique upstream process.…”
Section: Discussionmentioning
confidence: 74%
“…However, the expression and function of PIM3 in leukemia are relatively less understood. Previously, Ishikawa et al observed that PIM3 knockdown suppressed cell growth in T cell leukemia cell lines, 21 whereas Zhou et al compared PIM3 expression in AML patients before and after chemotherapy and observed that changes in this parameter during the treatment correlated with the patient’s remission status. 22 In this study, we performed both clinical data analyses and cell line studies to further elucidate the function of PIM3 in AML, and observed regulatory effects on proliferation, survival and chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MT2A helps regulate NF-kB activity by modulating expression of IkB-a and has been shown to play a role in transmitting inflammatory signals to the vascular endothelium [54,55]. PIM3, which encodes a serine/threonine kinase, is one of several regulatory kinases that can be induced by NF-kB, which functions upstream of IkB-a and can lead to further activation of NF-kB itself (canonical) [56,57]. These findings suggest a complex cellular environment within the lumen of unruptured IAs, in which inflammatory pathways, potentially activated by MCP-1, RANTES, MIG, Eotaxin, IL-8, and IL-17, are regulated through NF-kB mediated transcription and downstream signal transduction.…”
Section: Discussionmentioning
confidence: 99%